1993
DOI: 10.1111/j.1471-0528.1993.tb15309.x
|View full text |Cite
|
Sign up to set email alerts
|

The value of cytology and colposcopy in the follow up of cervical intraepithelial neoplasia after treatment by laser excision

Abstract: Objective To determine the value of colposcopic assessment in the follow up of cervical intraepithelial neoplasia (CIN) treated by laser excision. Design Retrospective analysis of case records of women with CIN treated by laser excision over the period 1986 to 1990. Setting A colposcopy clinic in a district general hospital. Subjects Five hundred‐forty consecutive patients with either CIN or microinvasion diagnosed on laser excision specimens. Results Of 452 patients followed up f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
5
1
Order By: Relevance
“…Another disturbing and perhaps related finding was the failure of the immediate postprocedure endocervical smear to detect residual dysplasia in six cases with histologically positive endocervical margins. Thus, although the value of cytologic smears for the follow-up of patients in the months following cervical conization has been proven in previous studies, 3,11 collection of cytologic samples immediately following conization was not of diagnostic value in this study, due largely to technical hindrances induced by the procedure itself.…”
Section: Discussioncontrasting
confidence: 39%
“…Another disturbing and perhaps related finding was the failure of the immediate postprocedure endocervical smear to detect residual dysplasia in six cases with histologically positive endocervical margins. Thus, although the value of cytologic smears for the follow-up of patients in the months following cervical conization has been proven in previous studies, 3,11 collection of cytologic samples immediately following conization was not of diagnostic value in this study, due largely to technical hindrances induced by the procedure itself.…”
Section: Discussioncontrasting
confidence: 39%
“…This is in agreement with previous reports. [13][14][15][16][17] Rasbridge et al found that a depth of involvement of crypts of > 1.7 mm was associated with recurrence of disease in 13 of 22 cases (59%). 15 In a recent study by Hulman et al, 20 equivocal excision was associated with high recurrence rates.…”
Section: Discussionmentioning
confidence: 99%
“…9 10 Certain factors have been associated with failure of treatment or recurrence of CIN. These include the presence of CIN at ectocervical and endocervical margins of resection, 11 12 involvement of endocervical glands, [13][14][15][16][17] large CIN lesions, 11 18 depth of the loop, 19 20 high grade of CIN, 21 and the age of the patient. 22 The development of invasive carcinoma following treatment by loop excision biopsy is considered a failure of treatment.…”
mentioning
confidence: 99%
“…Some authors recommend that follow-up with cytology only will identify those with residual disease (1 1,26,27). but others note cases of residual disease at colposcopy which were not identified by cytology (28). It is important to follow patients for at least I year as most residual disease will become obvious within this time, since the rate of recurrences then drops dramatically ( 13).…”
Section: Follow-upmentioning
confidence: 99%